1962
DOI: 10.1149/1.2425450
|View full text |Cite
|
Sign up to set email alerts
|

The Oxidation of Sputtered Tantalum Films

Abstract: The oxidation of sputtered tantalum films has been studied over a temperature range of 100°–600 °C in oxygen at a gas pressure of 7.6 cm of Hg. The results obtained by means of a vacuum microbalance are compared with data on bulk tantalum, and it is found the rate of oxidation and amount of oxidation is considerably smaller than the bulk. A logarithmic relation was found to represent the data best in the range 400°–600°C. The factors which may give rise to the differences found between the film and the bulk ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1963
1963
1981
1981

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This explains the high value of the resistance. Thin films when heated in air can also undergo an increase in resistance because of oxidation [88].…”
mentioning
confidence: 99%
“…This explains the high value of the resistance. Thin films when heated in air can also undergo an increase in resistance because of oxidation [88].…”
mentioning
confidence: 99%
“…In previous studies, the oxidation reaction has been reported as linear (10,13), parabolic (7), cubic (17), and logarithmic (9,11,12) for comparable temperatures but generally higher pressures and longer times than considered here. The higher pressures and longer reaction times would tend to mask the linear behavior observed in this study.…”
Section: Discussionmentioning
confidence: 61%